Basic Properties and Carbonation of Concrete Replaced with Different Binders - วารินทร์ใหล, บัญญัติ (Srinakharinwirot University Engineering Journal, 2018)
This study was aimed to study the basic properties and the carbonation depth of partially replaced concrete with fly ash, granulated blast-furnace slag (GGBS) and limestone powder in ordinary Portland cement (OPC). The results showed that the water requirement of paste with fly ash was lesser than that of OPC paste. While the water requirement of paste made with GGBS and limestone powder was higher when compared to that of OPC paste. Additionally, the setting time of paste with fly ash and paste with GGBS was higher than that of OPC paste, while paste with limestone powder was lesser when compared to that of OPC paste. Moreover, the slump of concrete with fly ash was higher than that of OPC concrete whereas the slump of concrete with GGBS and limestone powder was lesser when compared to that of OPC concrete. The compressive strength of concrete with fly ash and GGBS was less than that of OPC concrete, especially when replaced in large quantity. Also, the compressive strength of concrete with limestone powder was close to that of OPC concrete. The carbonation depth of concrete with fly ash and GGBS was significantly higher than that of OPC concrete. The carbonation depth of concrete mixed with limestone powder was close to or little higher when compared to that of OPC concrete. The carbonation depth of concrete in water curing condition was lesser than that of concrete in air curing condition. The longer carbon dioxide exposure of concrete resulted in a greater carbonation depth than that of concrete with shorter carbon dioxide exposure. Finally, it can be compared the basic properties and the carbonation depth of concrete with fly ash, GGBS and limestone powder with OPC concrete.